PENGARUH MODEL PEMBELAJARAN NUMBERED HEAD TOGETHER BERBANTU MEDIA PUZZLE UNTUK MENINGKATKAN HASIL BELAJAR KELAS IV - Dwinanda Ary Nugroho; Ary Susatyo Nugroho; Aries Tika Damayani (FKIP, PGSD, Universitas Slamet Riyadi, 2020)
The purpose of this research is to find out the influence of the application of NHT model assisted by Puzzle media to improve learning outcomes in thematic learning Theme 3 subtheme 1 Learning 1 at SD Negeri 01 Medono Pekalongan. The research design used is One-Group Pretest-Posttest Design. The results showed that the final study results (Posttest) had a higher average of 76,973 while in the initial study results (Pretest) had a lower average of 58,595. As for the calculation of t test value of 14.4055 with a table of 2.021, thitung > ttabel. Because thitung >ttabel means H0 is rejected, meaning significant t test is accepted. So, it can be said that the learning model Numbered Heads Together (NHT) Puzzle media can improve learning outcomes in the learning thematic Theme 3 subtheme 1 Learning 1 at SD Negeri 01 Medono Pekalongan.